PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MENGHADAPI PARIWISATA ERA DIGITAL - Valid Mayyis Ibrahim; Muhammad Alkirom Wildan (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The tourism industry has entered a new era, namely the digital era of tourism. The digital era of tourism forces tourist destination managers to innovate more in tourism management in line with changes in technological advances. One of the important roles in tourism management is the leadership role of tourism management organizations. One of the leadership styles that can be applied to deal with digital era tourism is transformational leadership. The purpose of this study is to find out whether transformational leadership has been implemented in Tlangoh Beach Pokdarwis to deal with digital era tourism or the 4.0 era, understanding of tourism that has entered the digital era, and strategies that can be applied to deal with digital era tourism. The research method used in this study is descriptive qualitative which aims to reveal a situation as it should be. The results of the study show that there are two dimensions of transformational leadership that have not yet been implemented by the Pokdarwis chairman, namely: intellectual stimulation and inspirational motivation. The understanding that tourism has now entered the digital era is also considered lacking in this research. Seeing these problems, there are three strategies that can be implemented to deal with digital era tourism. The strategy is to carry out positioning, differentiating, and branding of tourist destinations.